Death anxiety and its predictors among the companions of hospitalized patients with coronavirus disease 2019 - Mehrooz Alishah; Masoumeh Bagheri-Nesami; Seyed Robabeh Babaei; Mehrnoosh Alishah (Shahrekord University of Medical Sciences, 2021)
Background and aims: Death anxiety (DA) is associated with stress and impaired immunity and thereby, puts individuals at risk for coronavirus disease 2019 (COVID-19). The aim of this study was to assess DA and its predictors among the companions of hospitalized patients with COVID-19. Methods: This descriptive-analytical study was conducted in 2020 on 200 companions of patients with COVID-19 hospitalized in Imam Khomeini, BouAli, and Razi hospitals in Sari and Qaemshahr, Iran. Sampling was performed conveniently. Data were collected using a demographic and clinical characteristics questionnaire for patients, a demographic and clinical characteristics questionnaire for companions, and Templer DA Scale. The SPSS software (v. 21.0) was used for data analysis via the independent sample t test, chi-square test, Pearson's correlation analysis, and multiple linear regression analysis. Results: The mean score of DA was 47.21±10.62 (in the possible range of 15-75). Participants' DA had significant relationship with their gender, their patients' anorexia and arterial oxygen saturation, and COVID-19 among other family members (P<0.05). Participants' gender, patients' anorexia and arterial oxygen saturation, and COVID-19 among other family members significantly explained 0.066% of the total variance of DA (P=0.002). The strongest predictors of DA were arterial oxygen saturation (β=0.17; P=0.01) and gender (β=0.15; P=0.0). Conclusion: The companions of hospitalized patients with COVID-19 experience high levels of DA and hence, interventions are needed to reduce their DA.